Urban Economic Governance, Business and Globalisation: Australasia's 'Committee‐for‐[City]' Phenomenon. Issue 6 (25th June 2013) - Wetzstein, Steffen
Abstract This article explores the nexus between urban economic governance, business and globalisation in light of new empirical research about the emergence of 'Committee‐for‐[City]' entities in Australasia3. It critically reviews key claims of the international literature on business‐mediated urban economic governance from both structural and post‐structural urban political economy, business mobilisation and globalisation perspectives in order to test these largely northern hemisphere‐centric theories against new research findings on business as emergent political and policy actor in Perth, Melbourne, Sydney and Auckland. On the basis of a conceptualisation that contemporary 'at‐a‐distance' urban economic interventions are essentially discursive public–private partnerships, the paper highlights the important role of business interests in the context of a co‐opting and partnering state. Although it is found that established notions such as 'urban growth machines' and 'entrepreneurial governance' are (still) relevant to explain the nature and work of these new business governance actors in Australasia, the influence of globalising processes and the constitutive nature of the institutional and socio‐economic context must be more thoroughly acknowledged. The hybrid nature of the governing objectives pursued and the multiplicity of political projects at work mean that governance and investment outcomes resulting from business‐mediated urban economic interventions cannot be assumed but must be traced and evaluated in careful empirical investigations.